Combinatorial therapy of Zinc metallochaperones with mutant p53 reactivation and diminished copper binding - Zaman, Saif (Mol Cancer Ther, 2019)
Chemotherapy and radiation (C,R) are more effective in wild type (WT) p53 tumors due to p53 activation. This is one rationale for developing drugs that reactivate mutant p53 to synergize with (C,R). Zinc metallochaperones (ZMCs) are a new class of mutant p53 reactivators that restore WT structure and function to zinc-deficient p53 mutants. We hypothesized that the thiosemicarbazone, ZMC1, would synergize with (C,R). Surprisingly, this was not found. We explored the mechanism of this and found the ROS activity of ZMC1 negates the signal on p53 that is generated with (C,R). We hypothesized that a zinc scaffold generating less ROS would synergize with (C,R). The ROS effect of ZMC1 is generated by its chelation of redox active copper. ZMC1 copper binding (K(Cu)) studies reveal its affinity for copper is ~10(8) greater than Zn(2+). We identified an alternative zinc scaffold (NTA) and synthesized derivatives to improve cell permeability. These compounds bind zinc in the same range as ZMC1 but bound copper much less avidly (10(6) – 10(7)-fold lower) and induced less ROS. These compounds were synergistic with C and R by inducing p53 signaling events on mutant p53. We explored other combinations with ZMC1 based on its mechanism of action and demonstrate that ZMC1 is synergistic with MDM2 antagonists, BCL2 antagonists and molecules that deplete cellular reducing agents. We have identified an optimal Cu(2+):Zn(2+) binding ratio to facilitate development of ZMC’s as (C,R) sensitizers. While ZMC1 is not synergistic with (C,R), it is synergistic with a number of other targeted agents.